Blended Distance Learning: Search for an Optimal Format - I. V. Tsarenko (Цифровая трансформация)
Article is devoted to a search for an optimal format of blended distance learning. The questioning of distance learning students of Sukhoi State Technical University of Gomel was used as a main research method. One discipline from the academic learning program was studied using e-learning technology (on-line classes) whereas (while) others disciplines were studied using traditional classroom face-to-face learning technique. Thus, students using blended distance learning have opportunity to compare and estimate efficiency together with advantages of both educative techniques. On-line classes were held in the period between sessions using BigBlueButton program.It was found that student majority estimate blended distance learning as most efficiency learning technique; half of questioning students consider that the quality of face-to-face and on-line learning is equal. The main advantages and disadvantages of e-learning were analyzed. Highest student attendance of on-line classes between sessions in comparison with face-to-face classes during session time was found. Optimal amount of disciplines for on-line learning to organize blended distance learning were established. Best regime, time and intensity for on-line classes were determined. Results of these investigations may be useful to organize optimal format of blended distance learning as well as to choose subjects for on-line learning and to create comfortable schedule of distance classes.